Learning the language of the media through a didactic project based on the inverted class in the university context - Arroyo Martínez, Laura (Pulso. Revista de educación, 2020)
This paper describes the development of a didactic experience undertaken in a second grade group in the Translation and Interpreting degree at Rey Juan Carlos University. The project was aimed at helping students to learn the specific characteristics of mass media language. This project has been carried out through an inverted, cooperative class methodology supported by audiovisual elements. Highly satisfactory results were obtained since, as explained throughout the paper, students’ learning results were considerably improved compared to those of the previous year. The qualitative and quantitative comparison of the learning results has been possible due to the fact that we worked with this group the previous year. The obtained results lead to an overall highly remarkable satisfaction level with the project. We consider that dissemination of this proposal is of great use because it has shown great pedagogical validity for the sample group. In the same way, it is very useful since, with the corresponding content adaptations, it can be applied in different levels of the Spanish Language classroom.
Keywords: Spanish Language; Media; Flipped classroom; Audiovisual Technique